Citizen Monitoring to Promote the Right to Health Care and Accountability - Ariel Frisancho; Maria Luisa Vasquez (My University, 2014)
This Case Study highlights the role of citizen monitoring and engagement in designing and implementation of social policies and building a transparent and accountable health care system. It shows how a strategic alliance between citizen and civil society combined with international human rights framework can be used to strenghten the capacity of rural women's agency and improve the quality of health care services at the local level.
Report based on "Participatory Voices Project"- a joint venture between CARE-Peru and CARE-UK.
Keywords: Maternal and Child Health